Dynamics of difference in Australia : Indigenous past and present in a settler country - Merlan, Francesca (University of Pennsylvania Press, 2018)
Francesca Merlan examines the dynamics of difference that have existed between the settler majority and Indigenous minority of Australia, from the events of early exploration to the present, shedding light on their unequal and changing relations over time.